Effect of concentration, exposure time and temperature on the toxicity of sulphur dioxide (SO2) for Botrytis cinerea, a pathogen of table grapes - Mouton, Petra (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1991.